2010
DOI: 10.1002/macp.200900596
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced RAFT Polymerization of Thermoresponsive Hydrogel Films: Impact on Film Thickness and Surface Morphology

Abstract: Thin hydrogel films of the thermoresponsive polymer poly(N‐isopropylacrylamide) (pNIPAm) were prepared by electrochemically triggered reversible addition‐fragmentation chain transfer (RAFT) polymerization. Two different RAFT agents were employed, which work in either acidic or basic solution. In both cases, addition of RAFT agents had an influence on the thickness and the surface morphology of the films. At low concentration, the polymerization efficiency increased. At high concentration, the efficiency decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…4042 However, an electrochemically mediated RAFT ( e RAFT) is more challenging than e ATRP. Cu/L complexes for ATRP have a well-defined and reversible redox behavior, 43 whereas the electrochemical reactivity of RAFT agents is mostly unexplored, and could result in irreversible redox processes that cannot be exploited to generate radicals.…”
Section: Introductionmentioning
confidence: 99%
“…4042 However, an electrochemically mediated RAFT ( e RAFT) is more challenging than e ATRP. Cu/L complexes for ATRP have a well-defined and reversible redox behavior, 43 whereas the electrochemical reactivity of RAFT agents is mostly unexplored, and could result in irreversible redox processes that cannot be exploited to generate radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and co‐workers found both in experiments using mechanical spectroscopy on oligo(ethylene glycol) dimethacrylates and in corresponding simulations that networks, which were generated via the RAFT process, exhibit an increased homogeneity. We ourselves found that thin hydrogel films of the thermoresponsive polymer poly( N ‐isopropylacrylamide) (pNIPAm), prepared by electrochemically triggered RAFT polymerization, show a strongly enhanced homogeneity of the hydrogel surfaces as studied by AFM . Photocrosslinking, however, appears to be of higher industrial importance and in the field of UV‐initiated crosslinking RAFT polymerizations, systems with multifunctional methacrylates were studied by Zhuo et al, who found that the RAFT process has a considerable influence on the curing kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It allowed for the modification of proteins in order to tailor new hybrid materials [23][24][25]. Recently a new impulse has been given to ATRP by controlling the reaction using electrochemistry, so-called e-ATRP which had was previously also attempted in combination with reversible addition-fragmentation chain transfer (RAFT) polymerization [26]. By adjusting the electrochemical potential, this method reduces Cu(II) to Cu(I) in-situ and thereby controlling the amount of Cu(I) in the system, and hence control over the polymerization reaction even in combination with the presence of oxygen which was previously only possible with activators regenerated by electron transfer atom transfer radical polymerization (ARGET-ATRP) [27,28].…”
Section: Introductionmentioning
confidence: 99%